Exploring the relative impact of biological sex and masculinity–femininity values on information technology use. Issue 2 (1st February 2017) - Cyr, Dianne; Gefen, David; Walczuch, Rita
ABSTRACT: Previous studies in an e-commerce context suggest that there are biological differences (i.e. whether one is a man or a woman) with respect to perceptions of websites. In other research, there is evidence that psychological gender (i.e. values such as masculinity or femininity) likewise influences website perceptions. It is the aim of the current investigation to explore the possibility that both biological sex and psychological gender influence user perceptions, and to examine the predictive power of each on our model. To test these assumptions, we use an augmented technology acceptance model (TAM). To maximise variance in our sample, participants are selected from two countries that are significantly different in masculinity–femininity. As expected, psychological gender better predicted trust and TAM than biological sex. Moreover, this study validates that the masculinity–femininity dimension as originally developed by Hofstede [1980. Culture's Consequences: International Differences in Work-Related Values . Beverly Hills, CA: Sage] can be separated into two scales – one each for masculinity and femininity. The results suggest the need for additional research into the differentiation between psychological gender and sex.